2021
DOI: 10.1111/jhn.12943
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of nutrition interventions in improving frailty and its associated constructs related to malnutrition and functional decline among community‐dwelling older adults: A systematic review

Abstract: Background: The present study aimed to evaluate the effectiveness of nutrition interventions on frailty and factors related to frailty, including malnutrition, sarcopenia and functional ability, among community dwelling older adults. A secondary aim was to synthesise current clinical guidelines for the identification and management of frailty, and then identify whether they aligned with the findings of the literature review. Methods: A systematic literature review was undertaken using four electronic databases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 75 publications
0
21
0
1
Order By: Relevance
“…A diet rich in protein benefits health, aids in the recovery of sick people, and maintains functional status in elderly people (Prokopidis et al, 2022a). An efficient method for improving muscle growth and strength as well as overall physical performance in older persons is the combination of resistance training and post-exercise protein supplementation (Khor et al, 2022;Velasco et al, 2022). Vitamin D intake is critical for older adults because of its widely recognized links to bone health, muscle strength and function (Li et al, 2022;Prokopidis et al, 2022b;Wang et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…A diet rich in protein benefits health, aids in the recovery of sick people, and maintains functional status in elderly people (Prokopidis et al, 2022a). An efficient method for improving muscle growth and strength as well as overall physical performance in older persons is the combination of resistance training and post-exercise protein supplementation (Khor et al, 2022;Velasco et al, 2022). Vitamin D intake is critical for older adults because of its widely recognized links to bone health, muscle strength and function (Li et al, 2022;Prokopidis et al, 2022b;Wang et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…A narrative review that aimed to identify practical conclusions to support the interdisciplinary management of malnutrition in cancer patients suggested that knowledge sharing between oncologists and dietitians can help to successfully address and treat malnutrition in this population [31].…”
Section: Nutrition Supports For Preventing Malnutritionmentioning
confidence: 99%
“…En otra 48 , con una calidad de evidencia moderada, las intervenciones en nutrición (incluida la suplementación proteica) o combinada con actividad física producen un pequeño pero significativo efecto en medidas de función física y movilidad. En la de Khor 49 , las intervenciones multifactoriales fueron más eficaces que la nutricional aislada, en mejorar el estatus de fragilidad y rendimiento físico.…”
Section: Prevención De Fragilidad En La Persona Mayorunclassified